OPTIMIZATION OF PROCESS PARAMETERS FOR CULTIVATION OF BACTERIOPHAGES PROMISING FOR BIOLOGICAL CONTROL OF PHYTOPATHOGENIC BACTERIA OF GENUS PSEUDOMONAS - Pilipchuk, T.A.; Gerasimovich , A.D.; Ananyeva, I.N.; Kolomiets, E.I. (Eurasian Journal of Applied Biotechnology, 2021)
Cultural parameters of bacteriophages screened for lytic activity toward host bacterial strain P. helmanticensis BIM В-582 D were investigated. The following conditions were shown to be optimal for cultivation of indicator culture and it’s lysis by Pseudomonas phages BIM ВV-45 D, BIM ВV-46 D, BIM ВV-47 D, BIM ВV-50 D, BIM ВV-53 D, BIM ВV-61 D in laboratory fermenters ANKUM-3M: nutrient medium – fish meal hydrolysate broth, temperature – 28°C, stirrer agitation rate – 160 rpm, aeration rate – 1 l air/ l medium per min. Biopreparation produced under optimized conditions and composed of six afore-mentioned phages display high lytic activity both in regard to the host strain and to phytopathogenic bacteria Pseudomonas syringae.